(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical and paraclinical features of children with acute viral encephalitis treated for sequences at National Hospital of Acupuncture. Subjects and methods: Retrospective description of 140 pediatric patients with sequences of viral encephalitis at National Hospital of Acupuncture from January 2022 to December 2023. Results: The most common features of children with acute viral encephalitis were impaired perception and fever (100%); convulsions (64.29%); weakness and paralysis of limbs (61.43%); vomiting/nausea (57.86%); muscle tone disorders (54.29%) and headache/irritability (53.57%). Cerebrospinal fluid testing showed that 70.71% children were positive for Japanese encephalitis virus and 29.29% children were positive for Herpes simplex virus. Brain MRI results showed that 49.28% of children had parenchymal lesions in the cerebral hemispheres and pons; 29.29% had parenchymal lesions in the thalamus and hypothalamus; 16.43% had cortical and subcortical lesions in the frontal and temporal lobes; and 5% had cortical and subcortical lesions in both cerebral hemispheres. Conclusion: The clinical and paraclinical features of children with acute viral encephalitis are very diverse. Diagnosis must be based on a combination of clinical features, cerebrospinal fluid testing and brain MRI.